Hierarchical network structure as seen in container shipping liner services in the Caribbean Basin - Robert J. McCalla (Belgeo)
This paper concerns the network structure of container shipping services in the Caribbean Basin. It investigates Robinson’s (1998) concept of hierarchical networks in container shipping in which the higher the order of the network the fewer the ports and the fewer the connections among those ports. Three networks are defined based on the geographical reach of the carriers’ services: Intra-Basin, Americas’ region, and Inter-Oceanic. All three networks are quite similar, although there are differences in the number of ports served and the number of services and linkages among the ports of each net. Each net has a high degree of redundancy. Almost 40 per cent of the 88 ports in the basin belong to all three nets. It is not true that the higher the order the network, where order is defined by the geographical scale of service, the fewer ports and the fewer linkages. Defining hierarchical structure is elusive. Even the hub and spoke service structure is not immediately obvious.